WORD FORMATION PROCESS IN THE JAKARTA POST ‘CULTURE’ ARTICLE - Mustika Yanti; Rahma Yanti Hasibuan; Sry Rahayu Harahap; Syafitri Angrika; Emeliya Sukma Dara Damanik (Lexeme : Journal of Linguistics and Applied Linguistics, 2022)
This research aims to analyze word formation process in The Jakarta Post ‘culture’ article. This object research is interesting to be researched since it is a famous Indonesian news using English as language based. This research used qualitative method by selecting and collecting data in The Jakarta Post ‘culture’ article, then analyze the article with word formation process related to semantics study. The result shows that there are 8 examples of affixation, 6 examples of acronym, 2 examples of blending, 4 examples of borrowing, 2 examples of backformations, 1 example of coinages, 4 examples of abbreviations, 7 examples of compounding, and 1 conversion. The researcher concludes that the word formation process in The Jakarta Post ‘culture’ article is dominated by affixation and compounding.